2008
DOI: 10.1111/j.1365-2486.2008.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Lagged effects of experimental warming and doubled precipitation on annual and seasonal aboveground biomass production in a tallgrass prairie

Abstract: Global climate change is expected to result in a greater frequency of extreme weather, which can cause lag effects on aboveground net primary production (ANPP). However, our understanding of lag effects is limited. To explore lag effects following extreme weather, we applied four treatments (control, doubled precipitation, 4 1C warming, and warming plus doubled precipitation) for 1 year in a randomized block design and monitored changes in ecosystem processes for 3 years in an old-field tallgrass prairie in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 66 publications
(87 reference statements)
12
164
3
Order By: Relevance
“…Whenever possible, direct measurements by biomass harvesting should be preferred over biomass estimation by proxy (Fay et al, 2011;Sherry et al, 2008). 2.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever possible, direct measurements by biomass harvesting should be preferred over biomass estimation by proxy (Fay et al, 2011;Sherry et al, 2008). 2.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are longterm warming experiments (e.g. Saleska et al, 1999;Sherry et al, 2009), we know of no experiments in perennial grasslands that have manipulated growing season rainfall variability and warming for long enough to compare their effects to those of interannual climate variation. Grasslands are important and experimentally tractable systems for examining these issues because they cover approximately 40 % of the land surface, are rich and dynamic in biodiversity, are a globally important agricultural resource, and are at risk from degradation and habitat conversion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ANPP could exhibit a lagged response to precipitation, with current year production reflecting previous year production in addition to current year precipitation (e.g., Oesterheld et al 2001, Wiegand et al 2004, Arnone et al 2008, Sala et al 2012. Previous authors (Oesterheld et al 2001, Wiegand et al 2004) have demonstrated that lag effects can amplify or dampen precipitation variability, depending on the sequence of precipitation years ( Fig.…”
Section: Introductionmentioning
confidence: 99%